2006
DOI: 10.1186/1477-5956-4-4
|View full text |Cite
|
Sign up to set email alerts
|

Proteins pattern alteration in AZT-treated K562 cells detected by two-dimensional gel electrophoresis and peptide mass fingerprinting

Abstract: In this study we report the effect of AZT on the whole protein expression profile both in the control and the AZT-treated K562 cells, evidenced by two-dimensional gel electrophoresis and peptide mass fingerprinting analysis. Two-dimensional gels computer digital image analysis showed two spots that appeared up-regulated in AZT-treated cells and one spot present only in the drug exposed samples. Upon extraction and analysis by peptide mass fingerprinting, the first two spots were identified as PDI-A3 and stathm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…It has already been reported that molecular chaperones in Drosophila can be secreted into the extracellular space [ 12 ]. ER-localized heat-shock proteins, disulfide isomerases and inositol phosphatases have previously been reported as O -glycosylated in “simple cells” (S2-KO cell models without the ability of core-GalNAc elongation) and proteins from the heat-shock family 70 have already been identified as O -glycoproteins in Drosophila [ 13 , 14 , 15 ].…”
Section: Resultsmentioning
confidence: 99%
“…It has already been reported that molecular chaperones in Drosophila can be secreted into the extracellular space [ 12 ]. ER-localized heat-shock proteins, disulfide isomerases and inositol phosphatases have previously been reported as O -glycosylated in “simple cells” (S2-KO cell models without the ability of core-GalNAc elongation) and proteins from the heat-shock family 70 have already been identified as O -glycoproteins in Drosophila [ 13 , 14 , 15 ].…”
Section: Resultsmentioning
confidence: 99%
“…There are approximately 6,000–60,000 protein-encoding genes in a single prokaryote or eukaryote species‘ genome [36], and even a single tissue sampled from a single multicellular species contains hundreds or even thousands of distinct proteins [37]. In ecological assemblages that contain both microbes and macrobes, proteomic diversity likely will exceed 10 10 expressed proteins because— unlike the — genome the proteome of a multicellular organism is not constant during its lifetime, but changes ontogenetically [38] and in response to changing biotic and abiotic conditions [9]. …”
Section: Characterizing and Summarizing Proteomic Diversitymentioning
confidence: 99%
“…Of the more than 180 predicted extracellular proteins present in the reproductive secretory glands of male D. melanogaster , over 100 have been confirmed to be transferred to the female along with sperm (e.g., reviewed in Ravi Ram & Wolfner 2007a and Chapman 2008; see also Walker et al 2006; Chintapalli et al 2007; Findlay et al 2008, 2009; Takemori & Yamamoto 2009). Many of the transferred proteins fall into conserved protein classes found in the seminal fluid of most animals studied to date and include proteases, protease inhibitors, acid lipases, cysteine rich secretory proteins (CRISPs), and lectins (Mueller et al 2004; Ravi Ram & Wolfner 2007a).…”
mentioning
confidence: 99%